1996
DOI: 10.3109/00365529609010352
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids and Low Carbohydrate Diet for Maintenance of Remission in Crohn's Disease: A Randomized Controlled Multicenter Trial

Abstract: Omega-3 fatty acids did not show an effect on extending the remission in Crohn's disease. For the diet patients the question remains whether the noncompliant patients dropped out early because they sensed a relapse approaching or whether their condition deteriorated because they failed to comply with the diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(107 citation statements)
references
References 19 publications
(5 reference statements)
1
101
1
4
Order By: Relevance
“…We can speculate that perhaps fish oil and 5-aminosalicylic acid have synergetic effects, and also that patient compliance in the fish oil group decreased during the study and could have affected the clinical outcome. Lorenz-Meyer et al (1996) published data from a large placebo-controlled trial in 204 patients with CD. Patients were included after an acute relapse of their disease in which remission (CD activity index < 150) was obtained under steroid therapy.…”
Section: Crohn's Disease and Ulcerative Colitis N-3 Polyunsaturated Fmentioning
confidence: 99%
“…We can speculate that perhaps fish oil and 5-aminosalicylic acid have synergetic effects, and also that patient compliance in the fish oil group decreased during the study and could have affected the clinical outcome. Lorenz-Meyer et al (1996) published data from a large placebo-controlled trial in 204 patients with CD. Patients were included after an acute relapse of their disease in which remission (CD activity index < 150) was obtained under steroid therapy.…”
Section: Crohn's Disease and Ulcerative Colitis N-3 Polyunsaturated Fmentioning
confidence: 99%
“…In addition this difference was maintained at 12 months, with an incidence of remission of 59% in fish oil group versus 26% in placebo group (Belluzzi et al, 1996). However another studies have not found beneficial effects of n-3 fatty acids supplementation in IBD patients (Loeschke et al, 1996;Lorenz-Meyer et al, 1996). Studies about the effect of olive oil in IBD patients are limited and most of them used the olive oil as a placebo because n-9 M U F A w a s c o n s i d e r e d a s a n e u t r a l f a t .…”
Section: Trials In Human Patientsmentioning
confidence: 86%
“…In addition, a pilot study showed that the levels of the TFAs octadecenoate and hexadecenoate in subcutaneous adipose tissue were significantly higher in patients with Crohn's disease than in healthy individuals [28]. Numerous studies have reported that the composition of total fatty acids in the diet is an important factor influencing intestinal inflammation in IBD [4][5][6][29][30][31][32]. Our data suggest that patients with IBD should also be concerned with the proportion of the trans forms of fatty acids in their diet, because it is probably a significant risk factor for the progression or relapse of colitis.…”
Section: Discussionmentioning
confidence: 99%